The erotic element in the rewriting of the conquest and discovery of America in Abel Posse’s Daimón (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
The article is an analysis and interpretation of the erotic element in the novel Daimón. Based on this theoretical premise, it proposes a counter-discursive approach in which America is transfigured in an erotic space in which pagan time overlaps accepted temporality, unleashing a continuous critique that challenges the official truth of historical events.
Keywords: Eroticism; official history; counter-discourse; conquest of America